Sensation Seeking and Adaptation in Parabonauts - Collado, Aurélie; Hainaut, Jean-Philippe; Monfort, Vincent; Bolmont, Benoît (Frontiers in Psychology, 2018)
Evidence from extreme environments suggests that there are relationships between difficulties of adaptation and psychological factors such as personality. In the framework of microgravity research on humans, the aim of this exploratory study was to investigate inter-individual differences of parabonauts on the basis of quality of adaptation to the physical demands of parabolic flights. The personality characteristics of two groups of parabonauts with a different quality of adaptation (an Adaptive group, N= 7, and a Maladaptive group, N=15) were assessed using the Sensation Seeking Scale, Brief COPE and MSSQ-Short. Compared to the Maladaptive group, the individuals of the Adaptive group scored higher on Boredom Susceptibility (i.e., a subscale of the Sensation Seeking Scale), lower on scales of susceptibility to motion sickness (MSSQ-Short) and tended to score lower on Instrumental Support Seeking (i.e., a subscale of the Brief COPE). These results suggest that individuals of the Adaptive group are more intolerant to monotony, present an aversion to repetitive and routine activities, are less susceptible to motion sickness and less dependent on problem-focused strategies. These characteristics may have contributed to developing a certain degree of flexibility in these subjects when faced with the parabolic flight situation and thus, may have favored them. The identification of differences of personality characteristics between individuals who have expressed difficulties of adaptation from those who have adapted successfully could help to prevent the risk of maladaptation and improve the wellbeing of (future) commercial or occupational aerospace passengers. More generally, these results could be extended to extreme environments and professional and/or sports domains likely to involve risk taking and unusual situations.